2017
DOI: 10.1111/hepr.12971
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum uric acid level was a notable adverse event during combination therapy with sofosbuvir and ribavirin

Abstract: Elevated serum UA level was a notable AE associated with SOF/RBV therapy for CHG2. However, because of the small number of subjects, the exact frequency of AEs should be re-evaluated with larger cohorts. We need to remember that elevated serum UA level might develop during the therapy, especially at W1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…hyperuricemia, and fatigue, as well as genotoxicity and teratogenicity in younger patients. [30][31][32] Apart from a better safety profile, LDV/SOF, as an RBV-free regimen, has been associated with a better health-related quality of life (HRQOL) in chronic HCV patients both during and after treatment, compared with RBV-containing regimens. An analysis of 494 genotype 1 and genotype 2 HCV patients in Japan treated with LDV/SOF±RBV and SOF+RBV with similar HRQOL scores at baseline found that more AEs were experienced during treatment by those who received RBV-containing regimens compared to those who received RBV-free regimens (46% vs. 22%).…”
Section: Discussionmentioning
confidence: 99%
“…hyperuricemia, and fatigue, as well as genotoxicity and teratogenicity in younger patients. [30][31][32] Apart from a better safety profile, LDV/SOF, as an RBV-free regimen, has been associated with a better health-related quality of life (HRQOL) in chronic HCV patients both during and after treatment, compared with RBV-containing regimens. An analysis of 494 genotype 1 and genotype 2 HCV patients in Japan treated with LDV/SOF±RBV and SOF+RBV with similar HRQOL scores at baseline found that more AEs were experienced during treatment by those who received RBV-containing regimens compared to those who received RBV-free regimens (46% vs. 22%).…”
Section: Discussionmentioning
confidence: 99%
“…An animal study demonstrated that SUA levels may decrease after DAA treatment . Nevertheless, it has been suggested that SUA levels may increase via the performance of human studies . It should be noted that the sample sizes in the previous studies were small.…”
Section: Discussionmentioning
confidence: 94%
“…For example, the elevated SUA levels during ribavirin use may be misinterpreted, due to the hemolysis of red blood cells . Sofosbuvir has been proposed to affect the levels of xanthine oxidoreductase, which may cause the elevation of SUA levels . In the current study, the post‐treatment SUA levels were measured 3 months after the end of treatment, at which time the potential drug interferences may have been washed out.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations